2011
DOI: 10.1007/s00428-011-1140-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implication of types of tumor-associated macrophages in Hodgkin lymphoma

Abstract: To evaluate roles of tumor-associated macrophages (TAMs) for prognosis of classical Hodgkin lymphoma (CHL). Expression of markers for TAMs, CD68, HLA-DR, CD163, HLA-DR/CD68 (M1), and CD163/CD68 (M2) was immunohistochemically examined in 82 cases with CHL. Positively stained cells were counted and correlation of number of TAMs and patients' survival time was analyzed. Number of CD163+ cells and M2 cells was significantly correlated with shorter overall survival (P < 0.05), while it was marginally significant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
70
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 16 publications
6
70
1
3
Order By: Relevance
“…Pathologically, cHL is characterized by the presence of a small number of diagnostic Reed-Sternberg cells in a background of bystander reactive cells composed of lym-vestigators, including the present authors, validated the adverse prognostic impact of a high TAM content using immunohistochemical staining for CD68 and CD163 [5][6][7][8][9][10]. TAMs are believed to provide trophic factors that directly accelerate the growth and survival of malignant lymphocytes [11][12][13][14].…”
Section: Introductionmentioning
confidence: 61%
“…Pathologically, cHL is characterized by the presence of a small number of diagnostic Reed-Sternberg cells in a background of bystander reactive cells composed of lym-vestigators, including the present authors, validated the adverse prognostic impact of a high TAM content using immunohistochemical staining for CD68 and CD163 [5][6][7][8][9][10]. TAMs are believed to provide trophic factors that directly accelerate the growth and survival of malignant lymphocytes [11][12][13][14].…”
Section: Introductionmentioning
confidence: 61%
“…[1][2][3] So far, many clinical studies have revealed that the presence of TAMs are strongly correlated with a poor prognosis for cancer patients. [4][5][6] Macrophages mainly polarize into two phenotypes with different cytokine and growth factor production profiles. 7,8) Classically activated macrophages (M1 macrophages) have an interleukin (IL)-10 low and IL-12 high phenotype.…”
mentioning
confidence: 99%
“…Different cut-off points were used and accordingly the results are different. While, most studies reported association between high CD68+ TAM infiltration and poor survival outcomes (DFS, [5,19,[35][36][37][38]41] DSS, [13,19,36] or OS), [5,[35][36][37][41][42][43][44][45] fewer studies found that there no relation between high levels of CD68+ TAM infiltration and outcome. [16,26,39,40] The results from our study support the trend that higher CD68+ TAM infiltration in TAM can be used as a biological marker for stratification of patients with risk of adverse outcome.…”
Section: Discussionmentioning
confidence: 98%
“…[16,[37][38][39][40] Also high CD68 was not found to be independent predictor of primary treatment outcome. However, different studies reported different association of high CD68 with some clinicopathological findings as B symptoms, [38,41,42] age, [35,41] mixed cellularity subtype, [5,35,[41][42][43] primary treatment failure, [5,19,36,38] male sex, [35] bulky disease, [35] and IPS. [35,37,41] In our study, there was association between high CD68+ TAM infiltration and higher disease stage similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%